Diseño de un sistema de control interno en el micromercado la española ubicada en la provincia de Cotopaxi cantón Latacunga - Chango Reyes, Valeria Libeth (2016)
The objective of this research was to design an Internal Control System for the "Micromercado La Española" located in the Latacunga City Cotopaxi Province, which will allow achieving efficiency and effectiveness in all its administrative and commercial operations due to the company does not have an adequate internal control. For the analysis, the inductive-deductive, analytic-synthetic methods were applied as general methods of investigation. The application and analysis of investigative techniques, such as the personnel survey and the interview with the owner allowed to collect information to determine the shortcomings in which the company incurs in the development of its different commercial activities. It is necessary to indicate that according to the obtained results, a fundamental strategy for the improvement of the administrative process is proposed, the design of manuals of functions and procedures in which the staff' activities to develop are clear, considering the existing lines of authority within it, and they can fulfill in a correct way the guideline established in the manuals; once this proposal will be applied, the researcher intend to provide an adequate attention to the client generating trust on customers, suppliers, in the financial system and to optimize the resources that own the business, and by this way to contribute its development and positioning in the market of the Cotopaxi Province.